Patients' perceptions of nurses' communication in public hospitals of Harari Regional State, Eastern Ethiopia. (May 2022) - Bekele, Yazew; Worku, Teshager; Atnafe, Genanaw; Debella, Adera; Habte, Sisay; Goshu, Abel Tibebu; Assebe, Tesfaye
Introduction: The quality of nursing care has been evaluated using patient perception. Patients' participation in nursing care and decision-making is regarded as a prerequisite for effective clinical practice; however, poor communication can lead to incorrect diagnosis and delayed, or ineffective medical treatment. Objectives: This study sought to assess admitted adult patients' perceptions of, and factors influencing, nurse communication at public hospitals in Harar, eastern Ethiopia. Methods: Facility-based cross-sectional study was conducted among 377 admitted adult patients in Harar Town public Hospitals from 15 April to 30 May 2020. A proportionate stratified sampling technique was used to select the study participants. A pretested and structured questionnaire was used to collect data through a face-to-face interview and which were entered into EpiData and analyzed using SPSS. Bivariate and multivariate logistic regression analyses were conducted, odds ratio and confidence intervals were calculated and statistical significance was declared at p < 0.05. Results: This study outlined that the overall prevalence of good perception toward nurses' communication was 41.9% (95% confidence interval = 37.1%, 46.9%). Patients whose age group were 26–35 years (adjusted odds ratio = 0.46 (95% confidence interval: 0.24, 0.86), Being female patients (adjusted odds ratio = 1.89; 95% confidence interval: 1.20, 2.98), admitted in private room (adjusted odds ratio = 3.25; 95% confidence interval: 1.91, 5.51), patients who have family support (adjusted odds ratio = 2.56; 95% confidence interval: 1.16, 3.64), urban residence (adjusted odds ratio = 0.65; 95% confidence interval: 0.02, 0.66) and language difference (adjusted odds ratio = 0.61; 95% confidence interval: 0.40, 0.94) were statistically significant. Conclusion: This study pointed out that less than half of the study participants had good perceptions toward nurses' communication. As a result, increasing the number of health care providers who speak the same language as the patients and communication and behavioral change training must be prioritized.